2006 IEEE Symposium on Visual Analytics Science and Technology 2006
DOI: 10.1109/vast.2006.261437
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Network Traffic Analytics Using Query-Driven Visualization

Abstract: Realizing operational analytics solutions where large and complex data must be analyzed in a time-critical fashion entails integrating many different types of technology. This paper focuses on an interdisciplinary combination of scientific data management and visualization/analysis technologies targeted at reducing the time required for data filtering, querying, hypothesis testing and knowledge discovery in the domain of network connection data analysis. We show that use of compressed bitmap indexing can quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…It implements the fastest known bitmap compression technique [37,38], and has been demonstrated to be effective in a number of data analysis applications [39,40]. In particular, it has a number of efficient functions for computing conditional histograms [41], which are crucial for this work.…”
Section: High Performance Index/query For Data Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…It implements the fastest known bitmap compression technique [37,38], and has been demonstrated to be effective in a number of data analysis applications [39,40]. In particular, it has a number of efficient functions for computing conditional histograms [41], which are crucial for this work.…”
Section: High Performance Index/query For Data Miningmentioning
confidence: 99%
“…The visualization is then focused on the selected features, thus significantly reducing the amount of data presented to the user. The concept of QDV has been successfully applied to a wide range of applications, e.g., network traffic analysis [39] and visual exploration of LWFA simulation data [7].…”
Section: Query-driven and Feature-based Visualizationmentioning
confidence: 99%
“…For example, query-driven visualization (QDV) integrates database technologies and visualization strategies to address the continually increasing size and complexity of scientific data [38][39][40]. In QDV, large data is intelligently pared down by user-specified selection queries, allowing smaller, more meaningful subsets of data to be efficiently analyzed and visualized.…”
Section: : End Ifmentioning
confidence: 99%
“…Accelerated processing performance times are critical for many scientific applications, e.g. query-driven visualization (QDV) [38][39][40], where data can be presumed to be read once, cached by the OS, and queried repeatedly during analysis stages. In these applications, user workloads are driven more by processing performance times, which make up a larger percentage of the analysis workload, then by disk access times.…”
Section: Answering a Simple Range Querymentioning
confidence: 99%
“…First, the notion of performing network traffic analysis using statistics (e.g., histograms) rather than raw data led to a methodology that enabled exploration and data mining at unprecedented speed [42]. That study showed the use of these concepts to rapidly detect a distributed scan attack on a dataset of unprecedented size -2.5 billion records.…”
Section: High-performance Query-driven Visualizationmentioning
confidence: 99%